SNAP-Based Open Ecosystem Banking Business Model: An IMRAD Framework for Scalability, Fintech Collaboration, and API Monetization - Easter Borny Uliarta Tobing; Saripudin (ITB AAS Indonesia Surakarta, 2026)
Digital banks are increasingly transitioning from product-centric institutions to platform orchestrators that enable multi-actor financial ecosystems through standardized application programming interfaces (APIs). In Indonesia, Standar Nasional Open API Pembayaran (SNAP)—issued by Bank Indonesia—formalizes technical, data, security, governance, and risk requirements to support interoperability and safe collaboration in payment-related Open APIs Source. This study develops an IMRAD-based conceptual framework for a SNAP-based open ecosystem banking business model and explains how standardization can accelerate scaling, strengthen fintech partnerships, and unlock API monetization opportunities while maintaining regulatory alignment. Using a qualitative, document-driven approach, the research synthesizes SNAP regulatory materials with established literature on platform ecosystems, ecosystem governance, and API management capability. The analysis maps SNAP’s regulatory scope (interconnection/interoperability, information security, governance, and risk management) into actionable design dimensions for digital banks, including API portfolio structuring, partner onboarding mechanisms, consent/authorization controls, and third-party risk governance Source. The resulting framework highlights three strategic outcomes. First, SNAP reduces bilateral integration complexity by encouraging standardized interfaces and shared implementation practices, improving ecosystem readiness and time-to-market. Second, it enables scalable collaboration by clarifying stakeholder roles and governance expectations across banks, payment service providers, and non-bank partners. Third, it supports new revenue logics—such as usage-based pricing, tiered access, and value-added API services—by treating APIs as managed products within a governed platform. The study concludes that SNAP can function as a national-level “rulebook” for ecosystem banking, helping digital banks shift from standalone service providers to trusted enablers of Indonesia’s digital economy while balancing innovation, security, and compliance.